Comparative Effects of Organic and Inorganic Fertilizers on Soil Organic Carbon and Wheat Productivity under Arid Region. Issue 10 (30th May 2020) - Hammad, Hafiz Mohkum; Khaliq, Abdul; Abbas, Farhat; Farhad, Wajid; Fahad, Shah; Aslam, Muhammad; Shah, Ghulam Mustafa; Nasim, Wajid; Mubeen, Muhammad; Bakhat, Hafiz Faiq
ABSTRACT: Organic amendments in the soil perform better than synthetic fertilizers in regards to soil fertility and sustainable crop productivity. Experiments were conducted to compare the effects of organic and synthetic fertilizers on soil fertility and wheat ( Triticum aestivum L.) productivity. Soil fertility and protein contents of wheat grains (13.2% and 13.3% during 2005–06 and 2006–07, respectively) were improved by organic amendments. However, synthetic fertilizer (at the rate of 150, 100, and 60 kg ha −1 N, P2 O5, and K2 O, respectively) applications resulted in the maximum grain yield (4.05 and 4.46 t ha −1 during 2005–06 and 2006–07, respectively). The observed and simulated soil organic carbon (SOC) reasonably agreed during RothC model validation ( R 2 = 0.99). Economic analysis showed the maximum net profit and relative increase in income (729 US ha −1 and 309%, respectively) from inorganic treatment. Application of synthetic fertilizers increased grain yield and farm profit while organic manure enhanced grain quality. The RothC model had potential for determining the SOC in organic farming under arid environment.